Sulfonated electrospun polystyrene as cation exchange membranes for fuel cells - Noor M. Jalal; Akram R. Jabur; Mohammed S. Hamza; Shrok Allami (Energy Reports, 2020)
Fuel cells are one of important renewable energy sources represent scientific trends of contemporary researches that seek to find better alternatives to solve the negatives of organic fuels and biological damage to humans, environment and atmosphere. The most vital part in hydrogen fuel cells is the cation exchange membranes whose special and critical role. Cation exchange membranes have been prepared and characterized using expanded polystyrene (PS) from waste packaging. Electrospun polystyrene PS membranes were synthesized by electrospinning. The electrospun PS membranes were chemically modified by sulfonation reaction. Electrospun PS membranes were immersed in (20%) diluted sulfuric acid (HSO4), as a sulfonating agent, for different periods of 1, 2, 3, and 4 h. Sulfonating reaction successfulness was demonstrated by FTIR investigations.SEM and EDS were used to detect the sulfonating and desulfonating reactions regarding the sulfonating time. Ion-exchange capacity (IEC) and the proton conductivity were reported and discussed with respect to different sulfonation time. IEC increased with increasing the sulfonation time. Obtained results showed that the membrane sulfonated for 2 h have the highest IEC, which was equal to 2.857 mmol/g. The proton conductivities of electrospun membranes increased with increasing sulfonation time. Maximum proton conductivity was (8.8 x 10-4) S/cm resulted after 3 h sulfonation.
Keywords: 330; Electrospinning; Sulfonation; Expanded polystyrene; Ion exchange capacity; Proton conductivity